Effects of Acute Physical Exercise With Low and High Cognitive Demands on Executive Functions in Children: A Systematic Review. - Paschen, Linda; Lehmann, Tim; Kehne, Miriam; Baumeister, Jochen (Pediatr Exerc Sci)

Entstehen durch eine Blicktäuschung Kosten für den Angreifer? - Güldenpenning, Iris; Weigelt, Matthias; Kunde, W. (Abstractband der 51. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Die Blicktäuschung im Basketball: Einfluss des zeitlichen Versatzes zwischen Blick- und Kopfwendung auf den Täuschungseffekt - Polzien, A.; Güldenpenning, Iris; Weigelt, Matthias (Abstractband der 51. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Deceptive Actions - Güldenpenning, Iris; Weigelt, Matthias (Dictionary of Sport Psychology)

A General Algorithm to Calculate the Inverse Principal p-th Root of Symmetric Positive Definite Matrices - Richters, Dorothee; Lass, Michael; Walther, Andrea; Plessl, Christian; Kühne, Thomas (Communications in Computational Physics)
We address the general mathematical problem of computing the inverse p-th root of a given matrix in an efficient way. A new method to construct iteration functions that allow calculating arbitrary p-th roots and their inverses of symmetric positive definite matrices is presented. We show that the order of convergence is at least quadratic and that adaptively adjusting a parameter q always leads to an even faster convergence. In this way, a better performance than with previously known iteration schemes is achieved. The efficiency of the iterative functions is demonstrated for various matrices with different densities, condition numbers and spectral radii.

Inklusion im Nachwuchsleistungssport. Vereinbarkeit von Schule und paralympischem Leistungssport an Eliteschulen des Sports versus Regelschulen.

Molecular Beam Epitaxy Growth and Characterization of Germanium‐Doped Cubic Al x Ga 1− x N - Deppe, Michael; Henksmeier, Tobias; Gerlach, Jürgen W.; Reuter, Dirk; As, Donat J. (physica status solidi (b))

Erwerb motorischer und sensorischer Kompetenzen - Krause, Daniel; Ramme, Katharina; Weigelt, Matthias (Praktische Ausbildung in der Physiotherapie)

Stereoselective Alkyne Hydrogenation by using a Simple Iron Catalyst - Gregori, Bernhard J.; Schwarzhuber, Felix; Pöllath, Simon; Zweck, Josef; Fritsch, Lorena; Schoch, Roland; Bauer, Matthias; Jacobi von Wangelin, Axel (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Digitalisierung im organisierten Sport – Eine Analyse zur Nutzung digitaler Instrumente in Sportvereinen - Riedl, Lars; Ehnold, Peter; Schlesinger, Torsten (Sciamus - Sport und Management, 4)
Trotz hoher Aktualität und steigender Bedeutung liegen zum Thema Digitalisierung im Sportverein bisher kaum empirische Erkenntnisse vor. Der vorliegende Beitrag setzt sich mit folgenden Fragestellungen auseinander: (i) In welchem Umfang und zu welchem Zweck nutzen Sportvereine digitale Instrumente? (ii) Welche vereinsspezifischen Faktoren determinieren das jeweilige Nutzungsverhalten? Hierzu wurde eine Stichprobe von n=787 Sportvereinen aus Österreich und Deutschland generiert. Es zeigt sich, dass digitale Instrumente vor allem zur internen und externen Kommunikation sowie zur Bewältigung klassischer Verwaltungsaufgaben eingesetzt werden. Das Ausmaß der Nutzung hängt einerseits von vereinsexternen Bedingungen ab. So zeigt sich dahingehend ein Ländereffekt, dass in Deutschland digitale Instrumente stärker genutzt werden als in Österreich. Darüber hinaus haben Auflagen seitens der Verbände zur Verwendung bestimmter Software (z.B. für die Meldung von Wettkampfergebnissen) einen wichtigen Einfluss. Andererseits bestimmen vereinsinterne Faktoren wesentlich das Nutzungsverhalten. Positiv wirken vor allem die Vereinsziele ‚Engagement/Erfolg im Leistungssport‘ und ‚Wollen Vorreiterrolle bei der Digitalisierung einnehmen‘. Negativ wirken eine fehlende Strategie im Umgang mit digitalen Instrumenten sowie die Einschätzung, dass digitale Prozesse nicht zur eigenen Vereinskultur passen.

Die Funktion des Sports im Gesundheitsmanagement der öffentlichen Verwaltung - Sennefelder, Lisa

Hard X-ray spectroscopy: an exhaustive toolbox for mechanistic studies (?) - Schoch, Anke; Burkhardt, Lukas; Schoch, Roland; Stührenberg, Kai; Bauer, Matthias (Faraday Discussions)
The hard X-ray spectroscopy methods XAS, valence-to-core XES and higher solution XANES offer unique insights into organometallic reaction mechanisms.

Kompetenzorientierte, universitäre Laborpraktika - Das Paderborner Physik Praktikum (3P) - Bauer, Anna; Sacher, Marc (Phydid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung)

Operationalisierung der experimentellen Kompetenz (Physik)Studierender - Bauer, Anna; Reinhold, Peter; Sacher, Marc (Qualitätsvoller Chemie- und Physikunterricht – normative und empirische Dimensionen)

A Novel Lubricant Based on Covalent Functionalized Graphene Oxide Quantum Dots - Wolk, Andreas; Rosenthal, Marta; Neuhaus, Stephan; Huber, Klaus; Brassat, Katharina; Lindner, Jörg K. N.; Grothe, Richard; Grundmeier, Guido; Bremser, Wolfgang; Wilhelm, René (Scientific Reports)

Easily Accessible Protein Nanostructures via Enzyme Mediated Addressing - Rüdiger, Arne A.; Brassat, Katharina; Lindner, Jörg K. N.; Bremser, Wolfgang; Strube, Oliver I. (Langmuir)

Using Approximate Computing for the Calculation of Inverse Matrix p-th Roots - Lass, Michael; Kühne, Thomas; Plessl, Christian (Embedded Systems Letters)
Approximate computing has shown to provide new ways to improve performance and power consumption of error-resilient applications. While many of these applications can be found in image processing, data classification or machine learning, we demonstrate its suitability to a problem from scientific computing. Utilizing the self-correcting behavior of iterative algorithms, we show that approximate computing can be applied to the calculation of inverse matrix p-th roots which are required in many applications in scientific computing. Results show great opportunities to reduce the computational effort and bandwidth required for the execution of the discussed algorithm, especially when targeting special accelerator hardware.

Habitual Fructose Intake Relates to Insulin Sensitivity and Fatty Liver Index in Recent-Onset Type 2 Diabetes Patients and Individuals without Diabetes. - Weber, KS; Simon, MC; Strassburger, K; Markgraf, DF; Buyken, Anette; Szendroedi, J; Müssig, K; Roden, M; Group, GDS (Nutrients)

Body dissatisfaction in normal weight children – Sports activities and motives for engaging in sports - Grimminger-Seidensticker, Elke; Möhwald, Aiko Julia; Korte, J.; Trojan, J. (European Journal of Sport Science)

Dietary carbohydrates: a review of international recommendations and the methods used to derive them. - Buyken, Anette; Mela, DJ; Dussort, P; Johnson, IT; Macdonald, IA; Stowell, JD; FJPH, Brouns (Eur J Clin Nutr)